Photoactive layer formation in the dark for high performance of air-processable organic photovoltaics. (15th September 2021) - Maeda, Akihiro; Liu, Ruiyuan; Yu, Kilho; Lee, Shinyoung; Nakano, Kyohei; Takakuwa, Masahito; Zhang, Shipei; Tajima, Keisuke; Fukuda, Kenjiro; Umezu, Shinjiro; Someya, Takao
Abstract: Recent progress in organic photovoltaics (OPVs) has led to an increased importance of laboratory-scale fabrication in ambient air using solution processes. However, the effect of the existence of both ambient air and light during the formation of a photoactive layer on the performance of fabricated devices has not been elucidated thus far in detail. Here, we show that photoactive layer formation in completely dark conditions enables air-processable OPVs with a high power conversion efficiency. The degradation in OPV performance caused by the coexistence of air and room light was confirmed by systematically examining atmospheric and room-light irradiation conditions during the formation and drying of the photoactive layer. Moreover, the degradation rate was much faster than that in the case of dried solid photoactive layers exposed to room light in ambient air. The photoactive layer with non-fullerene acceptors showed a much slower degradation rate, owing to room light, than that with fullerene acceptors. Based on these findings, we demonstrate that by eliminating light during formation, slot-die-coated OPVs in ambient air show comparable performance to that of spin-coated OPVs in an inert glovebox.